2020
DOI: 10.1089/aivt.2020.0008
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal microRNAs Release as a Sensitive Marker for Drug-Induced Liver InjuryIn Vitro

Abstract: Introduction: In vitro models for liver disease suffer from the lack of well-established and sensitive biomarkers of cellular damage. MicroRNAs (miRNAs; small noncoding RNAs) represent potential biomarkers for the detection of drug-induced liver injury in vivo and in vitro. Altered physiological state caused by disease or tissue damage results in altered release of exosomal-or protein-bound miRNAs, detectable in body fluids and cell culture media. Materials and Methods: Here, we exposed 3D-HepaRG cultures to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…CYP3A4 is the most abundant isoform in the human liver, responsible for the metabolism of a large number of clinically used drugs (>50%) [ 60 ]. RIF is capable of transcriptionally inducing CYP3A4 and is a common method used to assess CYP induction and metabolic capacity of hepatocytes in vitro [ 44 , 61 , 62 , 63 ]. In accordance with our previous studies using a 3D HepaRG model, this cell line displays basal and inducible CYP3A4 activity in the MT [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CYP3A4 is the most abundant isoform in the human liver, responsible for the metabolism of a large number of clinically used drugs (>50%) [ 60 ]. RIF is capable of transcriptionally inducing CYP3A4 and is a common method used to assess CYP induction and metabolic capacity of hepatocytes in vitro [ 44 , 61 , 62 , 63 ]. In accordance with our previous studies using a 3D HepaRG model, this cell line displays basal and inducible CYP3A4 activity in the MT [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several miRNAs have been identified as potential DILI biomarkers in clinical samples, in vivo and in vitro models [ 25 , 32 , 38 , 39 , 40 , 41 , 42 , 43 ], including liver-specific miR-122-5p that is predominantly expressed by hepatocytes and released into the blood upon hepatocellular injury. APAP-induced liver injury is an example of DILI-elicited liver injury and miR-122-5p release [ 25 , 41 , 42 , 43 , 44 ]. A recent publication reported increased release of miR-122 from a bio-printed multicellular human model exposed to MTX [ 45 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Messner and others characterized exosomal microRNA-122 in methotrexate and acetaminophen-induced toxicity in hepatic stem cells, HepaRG. They confirmed that microRNA-122 can be used as a sensitive biomarker for DILI (Messner et al, 2020).…”
Section: Introductionmentioning
confidence: 69%
“…They also retained the ability to respond to TGF-β1 (1 ng/mL) stimulation, as shown by the decrease in albumin expression and the increase in the expression of α-SMA, that correspond to hepatocellular injury and HSC activation, respectively. Both are known events that occur during liver fibrosis progression [ 29 , 30 , 31 ]. In contrast, dissociation of MTs with Accutase and Accumax led to a lower number of functional HepaRGs, as indicated by the lower number of albumin positive cells following day 3 dissociation ( Figure 3 A).…”
Section: Resultsmentioning
confidence: 99%